The Influence of Climate Factors on the Determination of Seed Quality and Seed Purity of Scutelaria Comosa Seed (Texas Journal of Multidisciplinary Studies, 2022)
In this scientific article, the purity indicators of the blueberry plant were 70-84.0% compared to the total weight of the sorted seeds of the experiment (options 2, 3, 4). It was noted that the highest indicator was 84.0% in the 4th option of the experiment, 11.7% higher than the 2nd option, and 4.9% higher than the 3rd option.Among the experimental options, the highest seed energy and germination were recorded in the 4th option, that is, in the seeds collected on September 10 from the 3-year-old plant seedlings